A lifespan perspective on the dual career of elite male athletes. (November 2015) - Debois, Nadine; Ledon, Aurélie; Wylleman, Paul
Abstract: Objectives: The first aim of this study was to explore how elite male athletes having had a long duration as well as successful sport career perceived the transitional challenges occurring during as well as after their sport career. The second aim was to identify the factors that facilitated or constrained their development at different domains of development (i.e., athletic, psychological, psychosocial, academic/vocational). Design and method: Participants took part to retrospective semi-structured interviews yielding transcripts that were analyzed using both deductive and inductive analysis. Results: Qualitative analysis revealed a non-linear path to excellence with many normative as well as non normative transitions from the beginning of the athletic career to the post-career stage. Elements most frequently evoked to describe the course of life during athletic career referred mainly to the athletic domain, but also in a concurrent way to family life, psychosocial relationships as well as educative/vocational domains. These various elements were experienced in turn as factors facilitating as well as constraining the course of life of athletes depending the stage of the career. Conclusion: This study highlights the importance to adopt a developmental (i.e., from the beginning of the career to the post-career stage) as well as holistic (i.e., athletic, psychological, psychosocial, academic-vocational) perspective when considering the development of talented athletes. It suggests that understanding how elite athletes may experience as well as cope with ups and downs punctuating their athletic career is indivisible from other concurrent domains of life development. Highlights: Importance to adopt a holistic perspective when examining athletic career development. Successful sport careers follow a non-linear path. Different domains of development concurrently influence the path to excellence. Each domain of development may alternatively facilitate or constrain the path to excellence.